217k views
1 vote
–18 + 15x = 3(4x – 6) + 3x

User Marchemike
by
6.2k points

2 Answers

0 votes
-18 + 15x = 3(4x - 6) + 3x; 3 × 4x= 12x; 3 × -6= -18; -18 + 15x = 12x - 18 + 3x; 12x + 3x= 15x; -18 + 15x = 15x - 18;
The answer is infinite solution.

Hope this helps :)
User Jonas Berlin
by
5.3k points
4 votes
First we need to combine like terms:


-18 + 15x = 12x - 18 + 3x


-18 + 15x = 9x - 18

-18 = 9x - 18 - 15x


-18 = -6x - 18

0 = -6x (the 18's cancel)


0 / -6 = x


0 = x

User Erjiang
by
5.2k points